Percutaneous Tracheostomy - Al-Shathri, Ziyad; Susanto, Irawan (Seminars in Respiratory and Critical Care Medicine, 2018)
Tracheostomy is a commonly performed surgical procedure in intensive care units (ICUs). Over the past three decades, there has been a substantial body of evidence to suggest percutaneous tracheostomy (PT) is at least as safe as surgical tracheostomy (ST) in the hands of trained clinicians. In most institutions, PT is more readily performed at bedside than ST in the ICU; hence, PT is an attractive alternative to ST in the ICU. Bedside PT generates significant cost savings by eliminating operating room and anesthesia charges. Bronchoscopy is commonly used as a visual aid during PT. Ultrasound (US)-guided PT is gaining popularity. It can be used as an adjunct or alternative to bronchoscopic-guided PT, especially in hospitals where access to bronchoscopy remains fairly limited and US is more widely available. There are many benefits in converting translaryngeal intubation to tracheostomy. It is widely accepted that tracheostomy is preferred if there is an anticipation of prolonged need for an artificial airway. The timing of this conversion from translaryngeal intubation to tracheostomy remains a subject of controversy. Limited data are available regarding the safety of PT on patients who are on dual antiplatelet therapy or active anticoagulation. Given the heterogeneity of PT techniques, adequate training and experience with the technique, coupled with careful planning are essential in minimizing any potential complication.
Keywords: percutaneous tracheostomy; surgical tracheostomy; intensive care unit; bronchoscopy; ultrasound